Publisher Correction: Reconciling qualitative, abstract, and scalable modeling of biological networks - Loïc Paulevé; Juri Kolčák; Thomas Chatain; Stefan Haar (Nature Communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.